The Role of Islamic Religious Education in Preventing and Addressing Bullying in Elementary Schools - Habib, Hasnan; Prabowo, Yoga Sari (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2024)
This exploration is spurred by the rising peculiarity of tormenting in schools. This examination means to figure out the effect of harassing at the Tulungagung Islamic Primary School and the job of Islamic Strict Training in forestalling and defeating this tormenting peculiarity. The consequences of the exploration showed that understudies who were the objects of harassing felt apprehensive which was communicated by crying, understudies felt discouraged, understudies were hesitant to go to class and a close to home reaction happened by tormenting back at the main domineering jerk. The school's moves toward conquer existing harassing conduct are to complete general effort to all understudies, discuss seriously with the culprits of tormenting, include guardians or gatekeepers of understudies in taking care of tormenting cases and upgrade Islamic Strict Training subjects by executing Islamic-based programs. to all understudies. In this examination, the outcomes found that harassing conduct at SDI Imam Bukhori can be forestalled and overwhelmed with proof that the culprits of tormenting acts are receptive and ready to concede their slip-ups and apologize to understudies who are the objects of tormenting, understudies who have done tormenting acts. it is likewise simple to coordinate and teach through existing projects, instances of harassing can be smothered as instances of an understudy asking one more understudy for cash, making the understudy be apprehensive and not have any desire to go to class, instances of tormenting are done by something like 3 understudies in a timeframe for 1 year.